6y-2(y+1)=(y-2)+6

Simple and best practice solution for 6y-2(y+1)=(y-2)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-2(y+1)=(y-2)+6 equation:


Simplifying
6y + -2(y + 1) = (y + -2) + 6

Reorder the terms:
6y + -2(1 + y) = (y + -2) + 6
6y + (1 * -2 + y * -2) = (y + -2) + 6
6y + (-2 + -2y) = (y + -2) + 6

Reorder the terms:
-2 + 6y + -2y = (y + -2) + 6

Combine like terms: 6y + -2y = 4y
-2 + 4y = (y + -2) + 6

Reorder the terms:
-2 + 4y = (-2 + y) + 6

Remove parenthesis around (-2 + y)
-2 + 4y = -2 + y + 6

Reorder the terms:
-2 + 4y = -2 + 6 + y

Combine like terms: -2 + 6 = 4
-2 + 4y = 4 + y

Solving
-2 + 4y = 4 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-2 + 4y + -1y = 4 + y + -1y

Combine like terms: 4y + -1y = 3y
-2 + 3y = 4 + y + -1y

Combine like terms: y + -1y = 0
-2 + 3y = 4 + 0
-2 + 3y = 4

Add '2' to each side of the equation.
-2 + 2 + 3y = 4 + 2

Combine like terms: -2 + 2 = 0
0 + 3y = 4 + 2
3y = 4 + 2

Combine like terms: 4 + 2 = 6
3y = 6

Divide each side by '3'.
y = 2

Simplifying
y = 2

See similar equations:

| 7x+11=3(x+y) | | (3d)(3d)(d-7)=0 | | X+(X*0.75)=608 | | 5(x-4)-(12-x)=11+6(1+x) | | 28b-21/7 | | 78=15+21b | | (4z-1)(3-z)=0 | | f(x)=x^6+7x^3-8 | | (11b-3)-5(2b+2)=-3 | | X/7=7/6 | | -130=5(6m+5)+m | | 4x+59-63=12 | | 13=a+2 | | -5(3b+1)+(16b-1)=0 | | -155=31m | | 2x+4*2=2*(x+2) | | Z/5=4/3 | | 4x+6=7x+3(2-x) | | [10-20]-[-7]= | | 130=31m+25 | | 5.12-3.34x=2x-1.555 | | Log[3](-7-4x)=1 | | 5x+8x+11=180 | | 3.17x+1.11=2.8x | | 364=8b-5(8b+4) | | 5(a+2)(a-4)=0 | | -32-49-3x=-12x | | 9z^2-54z+76= | | 96=8(6-a) | | u=4.20-0.75s | | 6m-8=4-3m | | 12x-4(x+4)=3+5(4x+1) |

Equations solver categories